Funeral customs in nineteenth century Ireland - Albano, Diego (Trinity College (Dublin, Ireland). Department of History, 2012)
The first part of the thesis is dedicated to the funeral customs of the lower classes. Chapter one analyzes the ‘merry wake’ through a wide arrange of memorials and contemporary sources, stressing the importance of its psychological function, in the light of Sean Connolly’s and Ó Súilleabháin's studies. The lower classes’ attitudes towards tragic and ‘untimely deaths’ are also taken into consideration. The second chapter assesses the impact of the Famine on funeral customs, demonstrating that although the crisis disrupted such customs, it did not have a lasting effect.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin